2018
DOI: 10.26417/ejef.v2i2.p35-39
|View full text |Cite
|
Sign up to set email alerts
|

A Single Band Antenna Design for Future Millimeter Wave Wireless Communication at 38 GHz

Abstract: In this proposed paper, a single band microstrip patch antenna for fifth generation (5G) wireless application was presented. 28, 38, 60 and 73 GHz frequency bands have been allocated for 5G mobile communications by International Telecommunications Union (ITU). In this paper, we proposed an antenna, which is suitable for the millimeter wave frequency. The single band antenna consists of new slot loaded on the radiating patch with the 50 ohms microstrip line feeding used. This single band antenna was simulated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…It should be noted that the relative positions of the antennas in the pair of ports (1,2) are the same as those in the pair of ports (3,4); this leads to identical ECC and DG as shown in Figure 22. The same applies to antenna pairs (1,3) and (2,4) and, also, for antenna pairs (1,4) and (2,3).…”
Section: Coupling Coefficients Envelop Correlation Coefficients and Diversity Gainmentioning
confidence: 93%
See 2 more Smart Citations
“…It should be noted that the relative positions of the antennas in the pair of ports (1,2) are the same as those in the pair of ports (3,4); this leads to identical ECC and DG as shown in Figure 22. The same applies to antenna pairs (1,3) and (2,4) and, also, for antenna pairs (1,4) and (2,3).…”
Section: Coupling Coefficients Envelop Correlation Coefficients and Diversity Gainmentioning
confidence: 93%
“…The mm-wave frequency bands centered at 28, 38, 60, and 73 GHz have been allocated for 5G mobile communications by International Telecommunications Union (ITU) [2]. Bands of 59-64 GHz are allocated by the Federal Communications Commission (FCC) as an unlicensed band for short range and wireless communications of high speeds [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the MIMO antennas reported in [18][19][20] are observed with a compact size, their main limitations are their low bandwidth, low isolation, or gain. Likewise, antennas reported in [9][10][11][12][13][14][15] are lacking with MIMO features due to which the channel capacity is limited. The overall study concludes that the proposed antenna possessing an excellent MIMO functionality outperforms the existing antennas by covering the entire band, i.e., 37-40 GHz, dedicated to millimeter-wave 5G communication and providing a maximum isolation of −45 dB with an optimum gain and reasonable size.…”
Section: Mimo Performance Metricsmentioning
confidence: 99%
“…To tackle this problem, array or multiple-input multiple-output (MIMO) antennas are crucial [7,8]. In the literature [9][10][11][12][13][14][15], several millimeter-wave 5G antennas have been reported. It is observed that some of them are single-port antennas and a few array antennas.…”
Section: Introductionmentioning
confidence: 99%